Mineral Composition of Potted Cabbage (Brassica Oleracea Var. Capitata L.) Grown in Zeolite Amended Sandy Soil - Sindesi Olwetu A.; Lewu Muinat N.; Ncube Bongani; Mulidzi Reckson; Lewu Francis B. (Agriculture, 2021)
Vegetables are essential components in human diets because they are rich in vitamins, minerals, and dietary fibre. There is a growing interest in human nutrition enhancement through vegetable consumption to reduce micro mineral deficiencies, especially in households with low buying power. A greenhouse pot experiment was conducted to evaluate the effect of zeolite amendment on the mineral composition of cabbage (Brassica oleracea var. capitata L.), in relation to the soil chemical status. The experiment was carried out over two growing seasons (winter/spring) of 2018 and 2019. The treatments were in the ratios of 0:10, 1:9, 2:8, 3:7 zeolite to sandy soil, on a weight-to-weight basis. Zeolite improved soil chemical status (p < 0.05), except for soil iron (Fe) and phosphorus (P) contents. There was also a general improvement of macro minerals in cabbage with increased zeolite application, especially in the second season. Zeolite did not improve the micronutrients of the vegetable. This indicates that cabbage planted under zeolite amended soils provides no additional contribution to the fight against micronutrient deficiencies. However, zeolite showed potential for soil conditioning in soil macronutrients and soil pH.